FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN HAND HYGIENE MAHASISWA PROFESI NERS DI RUANGAN RAWAT INAP - Anisa Arifin; Safri Safri; Juniar Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Healthcare Associated Infecions (HAIs) are infections related to services in health facilities that are strongly influenced by the cleanliness of the students of nursing profession who are conducting clinical practice. Hand hygiene Compliance of the students of nursing profession is a fundamental behavior in the effort to prevent nosocomial infections and cross infection in improving safety and health in hospitals.The purpose of this study was to examine the factors related to the compliance of the students of nursing profession to do hand hygiene in preventing infection in the Inpatient Room of Arifin Achmad Hospital in Riau Province.The study was quantitative with analytical observation research method with a cross sectional approach. There were 77 respondents as the samples of the research. They were taken based on the inclusion criteria using purposive sampling technique. The measuring instrument used was a questionnaire of knowledge level, attitude, and supervision as well as an observation sheet on the implementation of 5 moments of hand hygiene.The analyses used were univariate analysis in order to know the frequency distribution and bivariate analysis using Chi square and alternative Fisher’s Exact Test.The statistical test results showed that there was no relationship between the level of knowledge and hand hygiene compliance with p value (0.288), there was a relationship between attitude and hand hygiene compliance with p value (0.002), and supervisory relationship with hand hygiene compliance with p value (0.000). The researchers suggested that students of nursing profession to increase awareness and obediently perform hand hygiene at 5 moments in preventing transmission of HAIs in the inpatient room.Keyword: Attitude, compliance, hand hygiene, knowledge, and supervision.